SU-8 as Hydrophobic and Dielectric Thin Film in Electrowetting-on-Dielectric Based Microfluidics Device - Vijay Kumar; N. N. Sharma (Journal of Nanotechnology)
Electrowetting-on-dielectric (EWOD) based droplet actuation in microfluidic chip is designed and fabricated. EWOD is used as on-chip micro-pumping scheme for moving fluid digitally in Lab-on-a-chip devices. For enabling this scheme, stacked deposition of thin dielectric and hydrophobic layer in that order between microchannel and electrodes is done. The present paper investigates the potential use of SU-8 as hydrophobic layer in conjunction of acting as dielectric in the device. The objective for the investigation is to lower the cost and a thin simplification in fabrication process of EWOD-based devices. We have done design and optimization of dimensions of electrode array including gap between arrays for EWOD micropump. Design and optimization are carried out in CoventorWare. The designing is followed by fabrication of device and analysis for droplet motion. The fabrication of the device includes array of electrodes over the silicon surface and embedding them in hydrophobic SU-8 layer. Water droplet movement in the order of microliter of spherical shape is demonstrated. It has been shown that an SU-8 microchannel in the current design allows microfluidic flow at tens of voltages comparable with costlier and more complicated to fabricate designs reported in the literature.